Direct dose correlation of MRI morphologic alterations of healthy liver tissue after robotic liver SBRT - Boda-Heggemann, Judit; Jahnke, Anika; Wenz, Frederik; Blanck, Oliver; Hildebrandt, Guido (Strahlentherapie und Onkologie, 2018)
For assessing healthy liver reactions after robotic SBRT (stereotactic body radiotherapy), we investigated early morphologic alterations on MRI (magnetic resonance imaging) with respect to patient and treatment plan parameters.